EFEK LITERASI FINANCIAL DAN FINANCIAL BEHAVIOR TERHADAP FINANCIAL SATISFACTION - Indra Mulia Pratama; Fernando Saragih; Veri Aryanto Sopiansah (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This research is motivated by the research of Hayes (2014) and the opinion of financial planning expert Emilie Goldman regarding financial satisfaction. The purpose of the study was to determine the factors that affect the level of financial satisfaction. The research subjects were all students of accounting education at the PGRI University of West Sumatra. Student's financial satisfaction was measured by a questionnaire. The data analysis technique used is inductive analysis using the classical assumption test in the form of normality test, heteroscedasticity test, autocorrelation test, and multicollinearity test. The research hypotheses were tested using the simultaneous effect test (F test) and partial test (t test). The results showed that financial literacy, and financial behavior, had a significant effect on financial satisfaction in accounting education students at the PGRI University of West Sumatra. The implication of this research is that adequate financial literacy is needed to increase financial satisfaction of accounting education students at PGRI West Sumatra University. As well as adequate training in order to improve the financial behavior of accounting education students at PGRI West Sumatra University.